Sorbian studies in Japan: trends and perspectives - Sasahara, Ken; Kimura, Goro Christoph (Slavia Occidentalis, 2012)
Sorbian studies in Japan: trends and perspectives Summary How does it come that Japanese scholars get interested in Sorbian studies? In this paper we review how Sorbian studies emerged and evolved in Japan, centering on the humanities – especially on linguistics and literature studies. Of course, motivations to work on Sorbian studies vary from scholar to scholar. But characteristic of the situation in Japan is that along with interested Slavists, not a few Japanese researchers on Sorbian studies have begun their study with a German studies background. This fact suggests that a joint approach from the German and Slavistic viewpoints may enrich Sorbian studies in Japan. At the end of this paper, the actual list of works on Sorbian themes by Japanese researchers written in languages other than Japanese is added as an appendix.